A new satellite communication bandwidth allocation combined services model and network performance optimization. (18th May 2016) - Lin, Wenliang; Deng, Zhongliang; Fang, Qin; Li, Ning; Han, Ke
Summary: With the rapid development of online to offline economy, new services compositions would take up a great part in the satellite communication. More and more new services compositions request more bandwidth and network resources, which lead to serious traffic congestion and low channel utilization. Suffering from isolated link connection and changeable delay under the satellite environment, current bandwidth allocation schemes could not satisfy with the demand of low delay and high assess rate for new satellite services. This paper focuses on bandwidth allocation method for satellite communication services compositions. The novel models of services compositions with single‐hop Poisson distribution are designed to simulate original traffic arrival. Isolated independent coefficients take an original distribution to adapt to isolated disconnections. Services queue waiting time would be judged by acceptable delay threshold. Models provide new services compositions with more precise arrival distributions. In order to improve traffic congestion, the method combined services models, and a network performance is proposed. Optimal reserved bandwidth is set according to the priority and arrival distribution of different services compositions, which classify services with feedback transmission performance. We design minimum fuzzy delay tolerant intervals to calculate delay tolerant threshold, which adapt random delay changes in the services network with delay tolerant features. The simulation in OPNET demonstrates that the proposed method has a better performance of queuing delay by 16.3%, end‐to‐end delay by 18.7%, and bandwidth utilization by 13.2%. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new satellite communication bandwidth allocation combined services model and network performance optimization has been proposed to improve network performance for new satellite services.